The fake genre in Latin American Art - Marzo, Jorge Luis (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2020)
This article analyses some Latin American artistic practices that make use of the fake genre as a format to explore and question the regime of authority and truth in the new public sphere that emerged with the mass media. The analysis of the techniques of fictionality, infiltration, camouflage and imposture in which the fake genre is based allows to understand the impulses of a relevant part of Latin American art and activism (as part of a global phenomenon) tending to subvert the systems of adherence and consensus, often supported by the severe codes applied to cultural disciplines.